2021
DOI: 10.1167/iovs.62.7.9
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Retinal Changes in Wild-Type C57BL/6J Mice Between 2 and 32 Months

Abstract: The purpose of this study was to extend our understanding of how aging affects normal retina function and morphology in wild-type C57BL/6J mice, by analyzing electrophysiological recordings and in vivo and post mortem anatomy. METHODS.Electroretinograms (ERGs), spectral domain optical coherence tomography (SD-OCT), and confocal scanning laser ophthalmoscope (cSLO) in vivo images were obtained from mice between the ages of 2 and 32 months in four groups: group 1 (<0.5 years), group 2 (1.0-1.5 years), group 3 (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 58 publications
11
21
0
Order By: Relevance
“…As expected, 2-year old mice (both IGF-1 knockdown and control) exhibited significant reductions in both dark adapted (rods, Figure 5F ) and light-adapted (cones, Figures 5G,H ) responses compared to young (3-month-old) controls. These findings are consistent with prior studies in C57BL/6 showing significant age-related loss in rod and cone function with little or no photoreceptor degeneration ( Li et al, 2001 ; Gresh et al, 2003 ; Samuel et al, 2011 ; Ferdous et al, 2021 ). IGF-1 KD mice were partially protected from age-related decreases in rod and cone function compared to control mice ( Figures 5F–H ), exhibiting scotopic a- and b- wave amplitudes and photopic b-wave amplitudes that were slightly higher than those in age-matched controls.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…As expected, 2-year old mice (both IGF-1 knockdown and control) exhibited significant reductions in both dark adapted (rods, Figure 5F ) and light-adapted (cones, Figures 5G,H ) responses compared to young (3-month-old) controls. These findings are consistent with prior studies in C57BL/6 showing significant age-related loss in rod and cone function with little or no photoreceptor degeneration ( Li et al, 2001 ; Gresh et al, 2003 ; Samuel et al, 2011 ; Ferdous et al, 2021 ). IGF-1 KD mice were partially protected from age-related decreases in rod and cone function compared to control mice ( Figures 5F–H ), exhibiting scotopic a- and b- wave amplitudes and photopic b-wave amplitudes that were slightly higher than those in age-matched controls.…”
Section: Resultssupporting
confidence: 92%
“…Incipient photoreceptor degeneration is often preceded by mislocalization of photoreceptor outer segment proteins such as rod and cone opsins, however, we observed no signs of this in 1 or 2-year-old IGF-1 KD animals (or age-matched controls, Supplementary Figure 1 ). Because retinal function does not correlate directly with retinal degeneration, and it has been well established that there is significant age-related loss of retinal function without significant structural degeneration ( Li et al, 2001 ; Gresh et al, 2003 ; Samuel et al, 2011 ; Ferdous et al, 2021 ), we also conducted scotopic and photopic electroretinography on 2-year-old animals to assess rod and cone function. As expected, 2-year old mice (both IGF-1 knockdown and control) exhibited significant reductions in both dark adapted (rods, Figure 5F ) and light-adapted (cones, Figures 5G,H ) responses compared to young (3-month-old) controls.…”
Section: Resultsmentioning
confidence: 99%
“…Several age-dependent cellular and molecular changes have been described in mouse retinas, such as, photoreceptor mislocalization (Sugita et al, 2020 ) and vascular and RPE changes (Hermenean et al, 2021 ). Regarding metrics captured by OCT, although some studies have found age-dependent alterations in mouse retinas, such as auto-fluorescence (Ferdous et al, 2021 ) and scattering diversity (Gardner et al, 2020 ), these cannot be directly compared with our results. Therefore, we can only speculate that some healthy age-dependent neural adaptations may be altered in transgenic animals.…”
Section: Discussionmentioning
confidence: 77%
“…However, it is worth noting that overall OFF-RGCs were significantly smaller than ON-RGCs in both age groups ( Figure 5H ) and the range of OFF-RGCs sampled in older eyes was narrower (0.93 × 10 5 –2.90 × 10 5 μm 3 ) than younger OFF-RGCs (0.65 × 10 5 –5.00 × 10 5 μm 3 ; Figure 5N ). It is less likely that the narrower range of OFF-RGCs was due to cell loss during normal aging as there was no significant cell nuclei reduction in the ganglion cell layer between 2 to 12 months of age ( Ferdous et al, 2021 ). Nonetheless, this narrower range of OFF-RGCs may have limited our capacity to find differences in OFF-RGCs with age.…”
Section: Discussionmentioning
confidence: 99%